Analisis Data Scopus : Penggunaan Media Animasi di PAUD Berdasarkan Aplikasi Bibliometrik - Nurhusni Kamil; Yuanita Anthon Sope (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2023)
The use of audio-visual media in the world of education is no stranger, even the progress of science and technology continues to encourage educational practitioners to make new innovations. This has also been done in the world of early childhood education. The use of audio-visual media designed in such a way as to make it look attractive has been widely used in learning in PAUD. It is not only applied to schools inside, even to learning in foreign schools. This can be seen from the data obtained from Scopus data. Data in Scopus regarding the use of audio-visual media can be accessed through a bibliometric application. An application that is used in the field of scientific studies, especially research. The research method used is in a qualitative form by using a library research. The purpose of this research is to obtain a picture of the use of audio-visual media in early childhood through Scopus data based on data analysis from bibliometric applications.